Tax Incentives : Using Tax Incentives to Attract Foreign Direct Investment - Morisset, Jacques (World Bank, Washington, DC, 2012)
The increasing mobility of international firms and the gradual elimination of barriers to global capital flows have stimulated competition among governments to attract foreign direct investment, often through tax incentives. This note reviews the debate about the effectiveness of tax incentives, examining two much-contested questions: can tax incentives attract foreign investment? And what are the costs of using them?